2021
DOI: 10.3389/fnins.2021.782786
|View full text |Cite
|
Sign up to set email alerts
|

Self-Administration of Right Vagus Nerve Stimulation Activates Midbrain Dopaminergic Nuclei

Abstract: Background: Left cervical vagus nerve stimulation (l-VNS) is an FDA-approved treatment for neurological disorders including epilepsy, major depressive disorder, and stroke, and l-VNS is increasingly under investigation for a range of other neurological indications. Traditional l-VNS is thought to induce therapeutic neuroplasticity in part through the coordinated activation of multiple broadly projecting neuromodulatory systems in the brain. Recently, it has been reported that striking lateralization exists in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 92 publications
(123 reference statements)
0
10
0
Order By: Relevance
“…Several limitations have to be acknowledged in this study. First, current studies (13,30) have shown the association between vagus nerve and the midbrain dopaminergic neurons. Nevertheless, the correlation between vagus nerve and neuron network in other locations has not been extensively studied and validated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several limitations have to be acknowledged in this study. First, current studies (13,30) have shown the association between vagus nerve and the midbrain dopaminergic neurons. Nevertheless, the correlation between vagus nerve and neuron network in other locations has not been extensively studied and validated.…”
Section: Discussionmentioning
confidence: 99%
“…The mean gray value of the images was measured to quantify the expression levels of TH, α-synuclein, and VMAT2 in the midbrain dopaminergic neurons using ImageJ software (NIH, USA). The range of dopaminergic neurons labeled by TH in the SN and VTA was used to draw the region of interest manually by raters blinded to the study, who also measured the mean gray value ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has highlighted vagally mediated signaling pathways that modify VTA DA neuron activity and related behavior (Han et al, 2018 ; Fernandes et al, 2020 ; Brougher et al, 2021 ). Dopamine 2 receptors are expressed within these pathways, and play an important role in modulating neurotransmission, particularly within the NTS (Kline et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%